CHANGING FACE OF MEDICARE'S NATIONAL COVERAGE DETERMINATIONS FOR TECHNOLOGY. (11th January 2016) - Chambers, James D.; Chenoweth, Matthew D.; Pyo, Junhee; Cangelosi, Michael J.; Neumann, Peter J.
Abstract : Objectives: The Centers for Medicare and Medicaid Services (CMS) issues National Coverage Determinations (NCDs) for medical interventions expected to have a significant impact on Medicare, the health insurance program for US citizens aged 65 years and older and certain people with disabilities under the age of 65 years. The objective of this study was to evaluate NCDs issued from 1999 to 2013 to identify key trends, and to discuss implications for future CMS policy. Methods: We used the Tufts Medical Center Medicare National Coverage Determination Database to examine characteristics of NCDs from 1999 through 2013. We examined various characteristics of NCDs, including: whether the intervention under review is used for prevention or treatment of disease, the type of intervention considered, evidence limitations cited by CMS, and coverage determination outcome. We evaluated longitudinal trends in categorical and continuous variables in the database, using Cochran-Armitage trend tests and linear regression, respectively. Results: We found that NCDs increasingly focus on preventive care (p = 0.072), pertain to diagnostic imaging (p = 0.033), and evaluate health education/behavioral therapy interventions (p = 0.051). CMS increasingly cites the lack of relevant outcomes (p = 0.019) and the lack of applicability of study results to the Medicare population (p < 0.001) as evidence limitations. CMS less often restricts coverage to certain population subgroups in NCDs (p < 0.001), but increasingly applies coverage with evidence development policies (p < 0.001). Conclusions: Identified trends reflect broader changes in Medicare as CMS shifts its focus from treatment to prevention of disease, addresses potentially overutilized technologies, and attempts to issue flexible coverage policies.